2019
DOI: 10.1186/s41016-018-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

What is the advance of extent of resection in glioblastoma surgical treatment—a systematic review

Abstract: Glioblastoma multiform (GBM) is the most common malignant brain tumor characterized by poor prognosis, increased invasiveness, and high relapse rates. The relative survival estimates are quite low in spite of the standard treatment for GBM in recent years. Now, it has been gradually accepted that the amount of tumor mass removed correlates with longer survival rates. Although new technique advances allowing intraoperative analysis of tumor and normal brain tissue and functional paradigms based on stimulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…Surgical morbidity will also be lower. Complete resection in surgery is not always feasible because of the location of the tumour and involvement of critical neurovascular structures that may compromise the patient's functional outcome if injured [41]. We previously reported that ATR-FTIR can also help discriminate tumour sub-types [30], so for patients with tumours in eloquent brain regions not suitable for resection, liquid biopsy may obviate the need for, and risk of, surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical morbidity will also be lower. Complete resection in surgery is not always feasible because of the location of the tumour and involvement of critical neurovascular structures that may compromise the patient's functional outcome if injured [41]. We previously reported that ATR-FTIR can also help discriminate tumour sub-types [30], so for patients with tumours in eloquent brain regions not suitable for resection, liquid biopsy may obviate the need for, and risk of, surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Extent surgical resection is known to be independently associated with survival outcomes of patients with glioblastoma [ 34 ]. Therefore, we next investigated the impact of GTR or STR on NKA, absolute NK cell counts, and distribution of NK and T cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have now shown that progression-free survival and overall survival can be improved with increasing the extent of resection. [16][17][18][19][20][21] Conversely, permanent neurological deficit from surgery can instantaneously negate any benefit from a surgical intervention and cause permanent harm. Our current practice takes a multimodal approach toward maximum safe resection.…”
Section: Discussionmentioning
confidence: 99%